Palliative care and quality of life needs and outcomes for Māori with cancer: what do we know?. (June 2023) - Jones, Rhiannon Mihi; Signal, Virginia; Smith, Moira; Stairmand, Jeannine; Davies, Cheryl; Gurney, Jason
There are access, treatment and morbidity inequities for Māori (Indigenous people of New Zealand) with cancer in Aotearoa (New Zealand). This includes inequities in quality of life and experiences of the palliative care setting for Māori. This review included 20 papers that were identified through a combination of our literature review and key informant surveys. In this review, we consider the context of palliative care and cancer quality of care for Māori, draw on evidence regarding access and challenges for Māori with cancer in the palliative setting and discuss how to achieve palliative care equity for Māori with cancer. In Aotearoa, palliative care has fundamental underpinnings based on westernised understandings of health with a focus on addressing physical health aspects. Our findings highlight the misalignment of this approach with regard to Māori with cancer in the palliative care setting and to being able to fulfil their right to good health.